Perancangan Sistem Perpustakaan Berbasis Web Menggunakan Framework Laravel - Supriyadi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
The development of the world of information technology in the current era of globalization is very important because at this time an educational institution or company cannot be separated from the use of computers as a sophisticated data processing tool. Information technology using highly sophisticated and modern computer technology will make it easier for us to process data which can save time, space and costs. The method used in the development of this Library Information System is the Extreme Programming (XP) development method. The stages of the Extreme Programming (XP) method are Planning, Design, Coding and Testing. Extreme programming is one of the methodologies of the agile software development approach that focuses on coding as the main activity at all stages of the development cycle that is more responsive to customer needs and builds software with better quality. The results of the SIMPEKU application test prove that the SIMPEKU application is user friendly so it is suitable to be implemented for libraries. The SIMPEKU application makes it easy for all parties, namely students or admins because it is very helpful in the process of borrowing and returning books. Conclusion With the borrowing feature in the digital library application, it adds to technological advances that make it more practical for students to borrow books and return books.